The impact of different weed control approaches on strawberry yield - Bjelošević Dragoslava; Delić Duška (Agroznanje, 2025)
Plant protection today is based on the principles of integrated plant protection. For many years, scientific research in the field of plant protection has been oriented towards the study of scientific foundations that are absolutely necessary for the successful implementation of integrated protection of plants against various harmful organisms. Using the examples of good practice and the results of scientific research, it has been shown in this paper how certain principles of integrated plant protection can be successfully incorporated into the integrated protection of strawberries against weeds. In the area of the Brčko District of Bosnia and Herzegovina, the village of Popovo Polje, a research was conducted for three years (2021, 2022, 2023) on several variations of strawberry production: plots with the soil covered with synthetic material, i.e. with black plastic film, plots where the soil was covered with organic material, in this case with straw, plots on which weed control was to be carried out with herbicides, and plots on which no soil covering or weed control was to be carried out. The research was conducted in greenhouses. The aim of the experiment was to determine whether there was a significant difference in the final strawberry yield, effect of weed control methods, or effect of weed control treatments, as well as to determine the interaction observed over the years. To calculate these, the yields achieved per strawberry plant shown in grams were used. The collection of fruits from different test plots and the formation of representative samples using the methods of inferential statistical processing led to results that represent a key indicator of the success of weed control and, ultimately, the success of the agricultural process.